Muscle Selection and Dosing in a Phase 3, Pivotal Study of AbobotulinumtoxinA Injection in Upper Limb Muscles in Children With Cerebral Palsy - Oleszek, Joyce; Tilton, Ann; Carranza del Rio, Jorge; Dursun, Nigar; Bonikowski, Marcin; Dabrowski, Edward; Page, Simon; Regnault, Benjamin; Thompson, Catherine; Delgado, Mauricio R. (Frontiers in Neurology, 2021)
Background: Guidelines recommend botulinum toxin-A in pediatric upper limb spasticity as part of routine practice. Appropriate dosing is a prerequisite for treatment success and it is important that injectors have an understanding on how to tailor dosing within a safe and effective range. We report upper limb dosing data from a phase 3 study of abobotulinumtoxinA injections in children with cerebral palsy. Methods: This was a double-blind, repeat-treatment study (NCT02106351). In Cycle 1, children were randomized to abobotulinumtoxinA at 2U/kg control dose or clinically relevant 8U/kg or 16U/kg doses. Doses were divided between the primary target muscle group (PTMG, wrist or elbow flexors) and additional muscles tailored to clinical presentation. During Cycles 2-4, children received doses of 8U/kg or 16U/kg and investigators could change the PTMG and other muscles to be injected. Injection of muscles in the other upper limb and lower limbs was also permitted in cycles 2-4, with the total body dose not to exceed 30U/kg or 1000U (whichever was lower) in the case of upper and lower limb treatment. Results: 212 children were randomized, of which 210 received ≥1 abobotulinumtoxinA injection. Per protocol, the elbow and wrist flexors were the most commonly injected upper limb muscles. Across all 4 cycles, the brachialis was injected in 89.5% of children (dose range 0.8-6U/kg), the brachioradialis in 83.8% (0.4-3U/kg), the flexor carpi ulnaris in 82.4% (0.5-3U/kg) and the flexor carpi radialis in 79.5% (0.5-4U/kg). Other frequently injected upper limb muscles were the pronator teres(70.0%, 0.3-3U/kg). adductor pollicis (54.3%, 0.3-1U/kg), pronator quadratus (44.8%, 0.1-2U/kg), flexor digitorum superficialis (39.0%, 0.5-4U/kg), flexor digitorum profundus (28.6%, 0.5-2U), flexor pollicis brevis/opponens pollicis (27.6%, 0.3-1U/kg) and biceps (27.1%, 0.5-6U/kg). AbobotulinumtoxinA was well-tolerated at these doses; muscular weakness was reported in 4.3% of children in the 8U/kg group and 5.7% in the 16U/kg group. Conclusions: These data provide information on the pattern of injected muscles and dose ranges used in this study, which were well-tolerated. Per protocol, most children received injections into the elbow and wrist flexors. However, there was a wide variety of other upper limb muscles injected as physicians tailored injection patterns to clinical need.